Symphony No. 4 in G Major for Soprano and Orchestra - Mahler, Gustav. 1860-1911 (Colección Dover Miniature Scores, 2000)
Mahler's Fourth Symphony ranks among the most beloved of his symphonic works and marks a distinct turning point in his approach to composition. It was here that he developed in its most sophisticated guise the idea of the "programme." In this case, the poetic idea is the progress from experience (the first movement) to the utterly innocent, childlike vision of Paradise ? the exquisitely serene vocal setting of the poem "Das himmlische Leben" (The Heavenly Life). Reproduced from the original Viennese edition ? with bar-numbered movements for easier reference ? this affordable, high-quality, conveniently sized volume is ideal for study in the classroom, at home, or in the concert hall and will be the edition of choice for music students and music lovers alike.